Young Investigator - Towards Creativity and Innovative Mind Through Inquiry Learning Using Qualitative Study - Hasmadi, Hassan; Mazeni, Ismail; Jameyah, Sheriff; Mohd Azuri, Shaari (American Scientific Publishers, 2018)
The aim of the study was to introduce Project Approach in early childhood education in rural pre schools in the district of Kota Bharu a town in the eastcoast of Malaysia. Most of the teachers of these pre schools does not have a formal training in early childhood education. Their knowledge and experience in early childhood education were through hands on and on the job training. The themes identified from the qualitative data analysis were (1) inquiry learning, (2) teamwork, and (3) communication. Using Project approach teacher is able to prepare new ideas to teach children using inquiry learning in preparing them to be young investigator.